Circles of support and accountability: the characteristics of core members in England and Wales - Clarke, Martin; Warwick, Leah; Völlm, Birgit (Wiley, 2016)
Background Circles of support and accountability, or Circles, use community volunteers to help reintegrate sex offenders at risk of reoffending in the community.